Application of economic analysis to decision-making processes in the field of innovation management (Economic and Political Thought, 2022)
The implementation of economic analysis into innovation management can be difficult to execute. This difficulty means that innovation will result in results different from those expected. The main purpose of this article is to show the applicability of recognized and widely used economic analysis tools for all aspects of investment in innovation. This article will also suggest a structure for implementing this type of investment evaluation analysis. The method of analysis and logical construction will be applied, and the considerations will be based on the key components of investment in innovation in the area of information systems.
Keywords: innovation, financial modeling, forecast analysis, model financial, manufacturing costs, forecasting, financial model, business plan projections, investment analysis, ROI assessment, tco, total cost of ownership